Materiali omogenei ed eterogenei alla scuola dell’infanzia - Vernassa, Karol; Turco, Francesca (Chimica nella Scuola, 2023)
The following manuscript reports a didactical unit aimed to lead kindergarten and primary school children in the exploration of some characteristics of materials. In particular, by means of an inductive approach and thanks to laboratory didactics, the children explore the homogeneity and the heterogeneity of materials starting from perceptions during their handling.